Determinants of cloud computing adoption by Romanian SMEs in the digital economy - Dincă, Violeta Mihaela; Dima, Alina Mihaela; Rozsa, Zoltán (Journal of Business Economics and Management, 2019)
The purpose of this paper is to explore the process of Cloud Computing adoption within Romanian Small and Medium sized Enterprises in the digital age. Most of the scientific papers related to this topic examine the general outlook of cloud computing implementation in Romania and focus on the use of the afore-mentioned technologies by large scale companies. In order to identify the factors that have an influence over the choice of Romanian SMEs to adopt cloud computing technology, a conceptual model has been set forth. The model’s dependent variable is the choice of the company’s management to implement cloud computing technologies. Five different independent types of variable structures which have an effect on the adoption of cloud computing within SMEs were identified. The five categories of variables are competition & government, ICT providers & firm departments, employee, manager and technological factors. Each of these categories of determinants encompasses at their turn two or more constructs.An online survey tested the model based on the responses of managers and directors from 198 Romanian SMEs from the cities of Bucharest and Cluj. The validity of the model was performed by completing factor analysis and reliability tests of the data; a logistic regression analysis was deployed to test the research hypotheses. The results emphasized that the managers’ know-how on cloud computing and the perceived costs of implementing the technology represent the main components influencing the spreading of cloud computing among Romanian SMEs. This study makes a valuable contribution to the academic environment but to businesses as well. The model can be used to examine the implementation of different innovative applications. Companies which offer cloud computing services could take advantage of the outcomes of this study to expand the degree of cloud service introduction among SMEs.